IDENTIFICATION OF MEDICINAL PLANTS AS IMPROVING BREAST MILK FOR BREASTFEEDING MOTHERS IN THE PAKPAK TRIBE KOTA SUBULUSSALAM - Cahaya Dinata; Cut Ratna Dewi; Nurlia Zahara (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2024)
Breast milk contains immune substances that provide protection against various diseases and also contains enzymes that will help digestion. The results of a pre-survey conducted in Desa Penanggalan, Kota Subulussalam, showed that the coverage of babies that receiving exclusive breast milk had not reached the target. One of the factors causing the low level of breastfeeding for babies is due to the lack of breast milk production coverage. This research aims to determine the type of plants used by the Pak-Pak people of Subulussalam and processing method. This type of research uses a qualitative approach with a purposive sampling method. Data collection techniques in the field are carried out using observation, structured interviews and documentation. The subjects in this research were all Pakpak tribal people from Penanggalan Village who used plants for the adequacy of post-natal breast milk and the object of this research were the types of plants used for the adequacy of post-natal breast milk. The research results showed that there were 16 species from 12 families. The most widely used plants are vegetables. The most common processing method is by boiling 75%, consuming 13% directly, processing it into food and extracting 6% each by the Pakpak tribe community, Penanggalan Village, Subulussalam City.